Time Varying Meshing Stiffness Analysis and Experimental Study of Fatigue Pitting Helical Gear based on Finite Element Method - Jinkai Li; Yong Chen; Libin Zang; Wangyang Bi; Xiaopeng Yang (Jixie chuandong)
Meshing stiffness calculation of fatigue pitting helical gear is an important basis of gear failure dynamics analysis. The finite element models of normal gears and fatigue pitting gears are established by using the finite element method to calculate the meshing stiffness of helical gears. Through the finite element model calculation，the normal contact force and comprehensive elastic deformation of the tooth surface are obtained. According to the calculation method of meshing stiffness，the single tooth meshing stiffness and multi tooth comprehensive meshing stiffness of the gear are obtained. The influence of different spalling length and width of pitting corrosion on the meshing stiffness of gears is analyzed. The results show that the spalling length and width have great influence on the meshing stiffness of gears，and the spalling length will affect the change area of meshing stiffness of gears. Through the fatigue pitting test，it shows that the reduction of gear meshing stiffness makes the gear vibration impact response increase.